Perdagangan Intra – Industri Indonesia Di Pasar Dunia - Hermanto Hermanto (Economic Journal of Emerging Markets, 2002)
Based on the empirical studies on intra-industry trade, Greenaway and Milner (1989) classified intra-industry trade in three categories: country-specific, industry-specific, and policy-based. This research will be focused for testing industry-specific hypothesis of intra-industry trade in Indonesia. By some reasons of intra-industry trade (IIT), product differentiation as the most important variable (Balassa, 1967; Grubel and Llyod, 1975).Descriptive analysis and econometric model were applied in this study to obtain a general conclusion about intra-industry trade in Indonesia and what the variables influence it. This analysis will be applied on the group of export product in manufacturing industries based on Standard International Trade Classification (SITC) and International Standard Industrial Classification (ISIC) in year 1980, 1985, 1990, 1995, 1996 and 1997.So, by the analysis that was applied in this research could be obtained some conclusions. First, the intensity of intra-industry trade in Indonesia is still low. This study shows that only 12 industries of 23 industries based on ISIC have an IIT more than 40 percent in 1980 - 1997. Secondly, the growth of IIT index and value shows the increasing trend. This condition indicates that Indonesia has a positive chance to more expansive in the future. Third, there are only 30 commodities (18,99 per cent) of 158 commodities that have a high IIT index in period 1980 – 1997. Forth, econometric analysis to intra-industry trade in Indonesia by industry-specific approach obtain the conclusion that product differentiation, scale economies in industry and market structure competitiveness in industry influences the intra-industry trade.Keywords: intra-industry trade, industry-specific, product differentiation